Limnological changes in South Carpathian glacier-formed lakes (Retezat Mountains, Romania) during the Late Glacial and the Holocene: A synthesis. (30th May 2018) - Tóth, Mónika; Buczkó, Krisztina; Specziár, András; Heiri, Oliver; Braun, Mihály; Hubay, Katalin; Czakó, Dániel; Magyari, Enikő K.
Abstract: Remains of aquatic biota preserved in mountain lake sediments provide an excellent tool to study lake ecosystem responses to past climate change. In the PROLONG project a multi-proxy study was performed on sediments of glacier-formed lakes from the Retezat Mountains, Southern Carpathians (Romania). The studied lakes (Lake Brazi and Gales) are situated on the northern slope of the mountain at different altitudes (1740 m and 1990 m a.s.l.). Our main objectives were 1) to describe the main limnological changes in these lakes during the last ca. 15, 000 years and 2) to summarize the environmental history of the studied lakes based on taxonomical and functional patterns of the biological proxies. For this synthesis we used the results of diatom and chironomid analyses, and indirect biotic and abiotic parameters, including sediment organic matter (LOI) content, geochemical element concentrations (Al, Ca, S, Sr) and biogenic silica content. Using multivariate numerical approaches we analysed changes in the assemblage structure of siliceous algae and chironomids, compared temporal patterns among proxies, examined the relationship between potential driving factors, chironomid and diatom assemblage changes and identified paleolimnological phases of the lake successions. Changes in assemblage composition and aquatic ecosystem state apparently followed summer insolation, local climatic conditions and local productivity changes driven by these. Diatom and chironomid assemblages generally changed in a similar direction and at a similar time within a lake, but differed to some extent between Lake Brazi and Gales. At both lakes the strongest variations were observed in the Late Glacial and the first half of the Holocene. The strongest Holocene assemblage changes took place in the earliest Holocene in Lake Brazi, but extended into the mid-Holocene in Lake Gales, following long-term insolation changes and climatic changes. In addition, three common zone boundaries were identified: at ca. 14, 200 and at ca. 6500 cal yr BP for every records and at ca. 3100 cal yr BP for diatom records in both of the lakes and for the chironomid record of Lake Brazi. This multi-proxy synthesis provides comprehensive data that increase our understanding of the past variability of lake ecosystem functioning and biodiversity in East-Central Europe.